2010
DOI: 10.1590/s1517-83822010005000001
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate solubilization potential and phosphatase activity of rhizospheric Trichoderma spp.

Abstract: Trichoderma sp., a well known biological control agent against several phytopathogens, was tested for its phosphate (P) solubilizing potential. Fourteen strains of Trichoderma sp. were isolated from the forest tree rhizospheres of pinus, deodar, bamboo, guava and oak on Trichoderma selective medium. The isolates were tested for their in-vitro P-solubilizing potential using National Botanical Research Institute Phosphate (NBRIP) broth containing tricalcium phosphate (TCP) as the sole P source, and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 12 publications
(13 reference statements)
5
57
0
2
Order By: Relevance
“…However, it is possible that the P that was retained in the mycelium is available for uptake by plant roots when the mycelium dies (Kapri and Tewari, 2010). Future studies should focus on understanding the balance between phosphorus that is solubilized and phosphorus that is absorbed by the fungi for their metabolism and to consider phosphorus uptake by plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that the P that was retained in the mycelium is available for uptake by plant roots when the mycelium dies (Kapri and Tewari, 2010). Future studies should focus on understanding the balance between phosphorus that is solubilized and phosphorus that is absorbed by the fungi for their metabolism and to consider phosphorus uptake by plants.…”
Section: Discussionmentioning
confidence: 99%
“…Growth promotion is commonly considered an indirect indicator of phosphate solubilization by a microorganism (Dupponois et al, 2006;Kapri and Tewari, 2010). Nonetheless, these characteristics could be more related to the production of phytohormones and growth-promoting substances than to phosphorus solubilization (Narloch et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…increased dry biomass of chickpea plants by 22-33% compared with non-inoculated control (Kapri and Tewari 2010). Previous studies showed that A. niger and Vibrio proteolyticus were the most active P solubilizing species of fungi and bacteria, respectively (Vassilev et al 2007).…”
mentioning
confidence: 88%
“…A halo zone surrounding the colony after fourth day of incubation at 30°C indicated P solubilization. Quantitative estimation of P solubilization was done according to Kapri and Tewari [12]. The strain was inoculated in 100 ml of NBRIP medium and kept incubated in a shaker (150 rpm, 30°C, 6 days).…”
Section: Screening Of Plant Growth Promoting (Pgp) Traitsmentioning
confidence: 99%